Semantically Unconnected Relational Schemes - Mateljan, Vladimir (Array, 2002)
By means of normalizing data the relational scheme is decomposed into several smaller and more regular sub-schemes. During the decomposition there should be no loss of information. Using the Aho, Beri and Ullman algorithm it is possible to prove that the initial set of information has been kept. Using Rissanen criterion of component independence, it is possible to prove the same thing in a far simpler and faster way. Therefore, Rissanen test is of extreme importance in the process of designing a database. We will show in the work that Rissanen test is sufficient but not a necessary condition in proving the reversibility of the decomposition of the relational scheme, i.e. we will show that the decomposition of the relational scheme can be reversible even if the Rissanen test is not met.